2017
DOI: 10.1109/ted.2017.2717924
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Dielectric Breakdown in High-Voltage GaN MIS-HEMTs: The Role of Temperature

Abstract: The MIT Faculty has made this article openly available. Please share how this access benefits you. Your story matters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…The role of temperature is also similar under AC and DC stress. As T increases, I G increases as expected and the time to breakdown decreases [3].…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The role of temperature is also similar under AC and DC stress. As T increases, I G increases as expected and the time to breakdown decreases [3].…”
Section: Resultssupporting
confidence: 73%
“…The devices under study are industrially prototyped depletion-mode AlGaN/GaN MIS-HEMTs grown on Si substrate. Previous DC stress studies on these devices revealed a gate insulator breakdown behavior consistent with TDDB in both forward bias (V GS,Stress > 0, V DS = 0 V) and reverse bias (V GS,Stress < V t , V DS > 0 and large) [3], [5], [6].…”
Section: Methodsmentioning
confidence: 52%
See 1 more Smart Citation
“…Most publications of MIS-HEMTs are based on research devices with nitride dielectrics [202]- [205] or Al2O3 [206] as the gate insulator [207]. The gate failure in most of these MIS-HEMTs shows the TDDB behavior [208]- [210]. A 20 years lifetime (100 pm, 130 o C) extrapolation is reported for a 0.2 mm 2 gate area at positive gate voltage of 9.4 V [202].…”
Section: A Gate Lifetimementioning
confidence: 99%
“…Several kinds of dielectrics had been employed as the gate insulator materials in GaN MISHEMT, including Al2O3 [4][5][6][7][8][9][10], HfO2 [11,12], HfSiO [13], ZrO2 [14][15][16][17][18][19][20], Ga2O3 [21], SiO2 [22,23], and SiNx [24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%